2007
DOI: 10.1016/j.ijid.2006.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory tract infections among Hajj medical mission personnel, Saudi Arabia

Abstract: The common practice among pilgrims and medical personnel of using surgical facemasks to protect themselves against ARI should be discontinued and regular use of alcohol-based hand scrubs should be more vigorously encouraged. Further research is needed to evaluate the protective value of N95 facemasks against ARI during the Hajj period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 5 publications
2
49
1
3
Order By: Relevance
“…Among the excluded articles, 19 were identified as not being RCT, however met other inclusion criteria . The level of evidence types consisted of seven level III‐2 studies (prospective/retrospective cohort, case control and quasi‐experimental) with the remaining studies being level III‐3 (retrospective cross‐sectional, cross‐sectional, historical observational).…”
Section: Resultsmentioning
confidence: 99%
“…Among the excluded articles, 19 were identified as not being RCT, however met other inclusion criteria . The level of evidence types consisted of seven level III‐2 studies (prospective/retrospective cohort, case control and quasi‐experimental) with the remaining studies being level III‐3 (retrospective cross‐sectional, cross‐sectional, historical observational).…”
Section: Resultsmentioning
confidence: 99%
“…21 The highest uptake was 92.8% observed by Al-Asmary et al among health care workers during Hajj in 2005. 24 Excluding these two studies (Elachola et al 21 and Al-Asmary et al 24 ), uptake rate among pilgrims has remained generally steady with gradual increase from 24% in 1999 to 64% in 2014 with minor fluctuations (Figure 2). Studies involving HCWs reported an uptake from 50% in 2009 to 92.8% in 2005.…”
Section: Uptake Of Facemaskmentioning
confidence: 96%
“…About 37% of the pooled samples were females, in individual studies the proportion of females ranged from 10% to 63%. Excluding three studies, which involved HCWs deployed at Hajj, [23][24][25] all other included studies involved Hajj pilgrims. The origin of the participants varied depending on the study, seven studies included multinational participants, while the other 18 were exclusive to participants from a single country of origin; seven out of 18 (38.9%) were from Saudi Arabia, 20,[23][24][25][26][27][28] According to study types 11 out of 25 were cohort studies, 1,2,22-24,28-33 another 11 cross-sectional studies, 21,[25][26][27][34][35][36][37][38][39][40] two trials (not necessarily RCTs) 18,20 and one case-series conducted as a qualitative study 41 (Table 1).…”
Section: General Descriptionmentioning
confidence: 99%
“…In a study conducted among 250 personnel (25.6% of whom were physicians or nurses) serving at 2 Hajj mission hospitals during the 2004 season, a 22.6% attack rate of acute respiratory infections during and after the Hajj was observed with acute respiratory infections defined by the association of at least 1 constitutional symptom (fever, headaches, and myalgia) and at least 1 respiratory symptom. 12 In a study conducted among 120 HCWs from the Saudi Ministry of Health (MOH) and other Hajj medical missions during the 2009 season, 10.6% reported respiratory symptoms during the Hajj, and 12.5% were found infected by at least 1 virus post-Hajj comparing to 7.5% pre-Hajj using a PCR assay. 6 All positive cases were due to rhinovirus, but 1 post-Hajj case was due to coronavirus 229E.…”
Section: Discussionmentioning
confidence: 99%